In El Batey, My Father's Foot Lit a Fire - Sophie Maríñez (Caribbean Studies Students' Union, 2017)
First published in The Caribbean Writer Volume 31 New Vistas: An Evolving Caribbean (2017): 91-93. "In El Batey, My Father's Foot Lit a Fire" is inspired by Juan Bosch's short story "Luis Pie," narrated from the perspective of Luis Pie's son.